A Major Orthopaedic Surgery in a Hundred-year-old Patient During Pandemic of COVID 19: A Case Report - KC, Kapil Mani; GC, Raju; Bhandari, Bishwash; Acharya, Samir (Nepal Orthopaedic Association Journal, 2023)
It has been undoubtedly assumed that COVID-19 imposes an immense economical and psychological trauma to all common people. It is also true that COVID-19 had been appeared like a “world war” for health care workers all over the world. However, either conservative or operative treatment were offered for all trauma patients even during that period. We report a 100 years old female patient with femoral shaft fracture who was treated with intramedullary interlocking nail with full precautions to prevent virus transmission during lock down period. The post and perioperative complications were uneventful and she was walking comfortably after surgery.